Correlation between carbapenem susceptibility in Pseudomonas aeruginosa and modified antibiotic heterogeneity index: a multicenter observational study using a surveillance platform - Keisuke Sawada; Takaaki Kato; Shuji Kono; Hiromi Kaneko; Hayato Nakano; Shinobu Inada; Tatsuya Isogawa; Tadahiro Shimizu; Namiko Takahashi; Haruki Takano; Hiroaki Chiba; Makoto Sugimoto; et al. (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract